Lateral distribution of endometriomas as a function of age - Abi Nader, Khalil (2007)
The lateral asymmetry of ovarian endometriomas, with a left-sided predilection, seems to disappear with advancing age. This asymmetry does not seem to persist in women >35 years of age.